Third Five Year Plan Half-Yearly Progress Report 1963-64 Government of Rajasthan - Planning Commission (Planning Commission, 1963)
As against the Third Five Year target of outlay or, the development programmes amounting to 236 crore the allotment for the year 1963-64 was fixed at Rs. 34.50 crore representing 14.62 percent of the total plan provision. Over the three years i.e. 1961-62, 1962-63 and 1963-64, 45.27 percent of the plan provision is earmarked to be spent while for subsequent two years, 54. 73 percent of the proposed development outlay i.e. Rs. 129.16 crore remained to be spent. Alike the previous two years the pattern of allotment during the current year conforms to the pattern laid down in the original plan of the State with the exception of Cooperation and Community Development, and Agricultural programmes inter changing their positions i.e. a larger proportion was to be spent on Cooperation and Community Development as is observed from the following table.
Directorate of Economics and Statistics Rajasthan, Jaipur